Modelling, simulation, exergy and economic analyses of thermal cracking of propane using CO2 and steam as diluents - Zhang, Yao; Yan, Hui; Chong, Daotong; Cordiner, Joan; Wang, Meihong (Computer Aided Chemical Engineering, 2024)
Introduction of diluents can increase the yield of valuable products and reduce the coking rate during thermal cracking of propane. Use of captured CO2 as diluent for the ethylene manufacturing is preferred to avoid high cost of CO2 transport and storage. A 1-dimentional pseudo-dynamic model of plug flow reactor (PFR) was developed and implemented in gPROMS ModelBuilder®. The model was validated with industrial data. Economic and exergy analyses of the PFR using steam or CO2 as diluent were then carried out. The results indicate that using CO2 as diluent can increase the run length of PFR by 13.0% and annual profit by 10.20%. When operating at the ratio achieving highest annual profit, using CO2 as diluent can reduce exergy destruction by 20.53%. The key findings from this study indicate that using CO2 as alternative diluent has high potential to increase the profit and reduce energy consumption for ethylene manufacturing. Further study will focus on the effects of diluent-to-propane ratio using different diluents and the potential of using mixed diluents.